The mode of deformation in a cold-swaged multifunctional Ti-Nb-Ta-Zr-O alloy - Guo, W.; Quadir, Md Zakaria; Ferry, M. (2013)
Multifunctional titanium alloys, termed Gum Metal™, are ß-phase Ti alloys first developed in 2003. These alloys exhibit many interesting properties including, for example, low rate of work-hardening and superplasticity during cold deformation. The original report described a new plastic deformation mechanism not involving major dislocation activity to explain such deformation behavior. In the current study, a comparable Ti-36.8Nb-2.7Zr-2.0Ta-0.44O (wt pct) alloy to the original investigators was produced by powder sintering, hot forging, solution treatment, and cold swaging with the aim at investigating the microstructural development during swaging. XRD and TEM showed that the forged/solution-treated alloy was ß-phase with a small amount of ?-phase. After cold swaging by up to 96 pct area reduction, TEM/HRTEM revealed the existence of dislocations, deformation twins, ?-phase, nanodisturbances, and lattice bending, with EBSD showing the grains to be highly elongated in the swaging direction, fragmented, and distorted. Most notably, swaging also generated a strong âŒ© 110âŒo fiber texture, even after moderate strains. The foregoing structural analysis provides substantial evidence that dislocations are present in the alloy after cold swaging. The major support of dislocation glide processes acting as the dominant plastic deformation mode in the swaged alloy is the strong âŒ©110âŒo fiber texture that develops, which is a characteristic feature of all cold-drawn/swaged body centered cubic metals and alloys. © 2013 The Minerals, Metals & Materials Society and ASM International.